Polyphenol-Rich Extracts of Traditional Culinary Spices and Herbs and Their Antibacterial Activity in Minced Beef. (16th December 2019) - Akhtar, Saeed; Waseem, Muhammad; Ahmad, Nazir; Ismail, Tariq; Ahmad, Zulfiqar; Manzoor, Muhammad Faisal; Siddeeg, Azhari
Abstract : This study was conducted to elucidate minced beef stabilization properties of hydroalcoholic extracts of commonly used culinary spices from Pakistan against meat oxidative stress and microbial spoilage. Hydroalcoholic extracts of six selected spices, namely, onion, ginger, turmeric, coriander, fennel, and mint, were evaluated to inhibit microbial growth in minced beef under refrigerated storage (4°C) of nine days. Maximum phenolic concentration, i.e., 70.8 mg GAE/100 g, and free radical scavenging activity (75.9%) were anticipated by hydromethanolic extracts of ginger. The results propose that the addition of hydroalcoholic extracts of ginger and coriander @ 6.0% anticipate significantly (p < 0.05 ) higher inhibitory effects against Staphylococcus aureus and Escherichia coli . The results of this research conclude that the utilization of hydroalcoholic extracts may serve as a promising approach to preserve microbiological as well as the oxidative quality of minced beef and products of meat origin.